Analisis Kemampuan Pemecahan Masalah Berbasis Etnomatematika pada Tari Boran dan Caping Ngancak di SMP Ditinjau dari Gaya Belajar Siswa - Abidin, Zainal; Faridah, Luluk; Rohim, Abdur (Papanda, 2025)
Students' mathematical problem-solving abilities tend to be low because learning has not accommodated differences in learning styles and the lack of integration of local cultural elements in the context of the material being studied. This study was conducted with the aim of describing ethnomathematics-based problem-solving abilities in the Boran and Caping Ngancak dances as viewed from the perspective of students' learning styles. The research method used was descriptive qualitative. The research subjects were 6 ninth-grade students selected using a purposeful sampling technique based on the results of a learning style questionnaire. The data analysis technique used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data were obtained through a learning style questionnaire, ethnomathematics-based problem-solving tests in the Boran and Caping Ngancak dances, and interview guidelines based on Polya indicators. The results showed that students with visual learning styles were able to fulfill all indicators of problem-solving abilities. Students with auditory learning styles only fulfilled two indicators, namely planning and implementing a solution plan. Meanwhile, students with a kinesthetic learning style were only able to fulfill one indicator, namely implementing a plan/solving a problem. This study shows the influence of learning styles on the achievement of problem-solving ability indicators in the context of ethnomathematics, so it is important for teachers to accommodate differences in learning styles in contextual learning.